2005
DOI: 10.1002/cncr.20827
|View full text |Cite
|
Sign up to set email alerts
|

Loss of function of p16 gene and prognosis of pulmonary adenocarcinoma

Abstract: BACKGROUND Stepwise progression of peripheral‐type lung adenocarcinoma was characterized morphologically and was related to prognosis. Expression of the tumor suppressor gene p16 in pulmonary adenocarcinoma decreased, mainly as a result of aberrant methylation of the CpG islands of the promoter region. METHODS Aberrant methylation status of the p16 promoter region, the expression of its product, and loss of heterozygosity (LOH) on 9p21 were examined in surgically resected lung specimens from 57 patients (28 ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
44
1
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 17 publications
3
44
1
1
Order By: Relevance
“…Methylation of p16 has been linked with poor clinical outcome in bladder tumors, colorectal cancer, and lung cancer. 31,32 In our study, and unlike previous reports, 33 we were unable to observe any major effect of p16 methylation on overall survival and progressionfree survival. Compared with previous studies, our survival analysis was performed on a large cohort of patients uniformly treated in a clinical trial setting with long-term follow-up such that there is minimal censoring.…”
Section: Discussioncontrasting
confidence: 56%
“…Methylation of p16 has been linked with poor clinical outcome in bladder tumors, colorectal cancer, and lung cancer. 31,32 In our study, and unlike previous reports, 33 we were unable to observe any major effect of p16 methylation on overall survival and progressionfree survival. Compared with previous studies, our survival analysis was performed on a large cohort of patients uniformly treated in a clinical trial setting with long-term follow-up such that there is minimal censoring.…”
Section: Discussioncontrasting
confidence: 56%
“…In our study, the loss of p16 expression was detected in 32 of 51 (62.7%) patients with gallbladder cancer. In addition, the loss of p16 expression has been correlated with tumor progression or with decreased survival among patients with carcinoma of the lung, pancreas and esophagus, and malignant melanoma [21,22,24] . The correlation between p16 expression and clinicopathological factors is controversial.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that aberrant p16 promoter methylation is smoking habit associated, however TSGs methylation in non-smoker subjects has been detected [Liu et al, 2006;Nakata et al, 2006]. In addition, p16 promoter methylation has been shown to correlate with the progression of the malignancy in LC patients [Tanaka et al, 2005]. Taken together, p16 inactivation by promoter hypermethylation may be a useful precocity marker of LC development in high-risk subjects such as heavy smokers.…”
Section: Introductionmentioning
confidence: 99%